2022
DOI: 10.1108/md-12-2021-1654
|View full text |Cite
|
Sign up to set email alerts
|

Can sustainable practices protect investors during financial market instability? A multi-sector analysis during the COVID-19 pandemic

Abstract: PurposeThe aim of this study is to analyse the relationship between firms' sustainable practices and corporate financial performance during the COVID-19 pandemic. Specifically, this study aims to analyse the effect of sustainable practices on firms' stock returns during and after the first COVID-19 pandemic emergency.Design/methodology/approachA quantitative study was conducted to determine the impact of sustainable practices on firms' stock returns, using a sample of 1,418 European listed firms. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…The efficacy of ESG as a crisis-mitigation strategy was established in the literature during the 2008 financial crisis (Cornett et al , 2016; Lins et al , 2017). Therefore, when faced with a crisis that emphasized sustainability, ESG became viewed as a solution to alleviate the adverse effects of the pandemic on business value (Nirino et al , 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The efficacy of ESG as a crisis-mitigation strategy was established in the literature during the 2008 financial crisis (Cornett et al , 2016; Lins et al , 2017). Therefore, when faced with a crisis that emphasized sustainability, ESG became viewed as a solution to alleviate the adverse effects of the pandemic on business value (Nirino et al , 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This nevertheless has created the need to comply with principles of sustainable development and socially and environmentally responsible behavior to reduce the negative impact of infrastructure development on the environment, to be precise. Besides, studies have shown that real-estate companies complying with environmental regulations and CSR practices are found to have a good reputation in the market, which positively affects their business performance [21,59]. As per Shanyu [39], the impact of CSR on the sustainable performance and activities of businesses is found to be positive in BRICS countries.…”
Section: -4-csr and Real-estate Marketmentioning
confidence: 99%
“…In the real estate market, the profitability of BRIC companies is positively affected by corporate governance and sustainable policies that endorse stock returns. However, concerns regarding still exist regarding the environmental challenges and risks associated with the massive books in the real-estate sector [59].…”
Section: -4-csr and Real-estate Marketmentioning
confidence: 99%
“…, 2020). In fact, the pandemic had a huge impact not only on the economy but also from a social point of view (Nirino et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This led to the necessity for a reconsideration of organizational strategies both in developed and emerging countries (Battisti et al, 2022), as the magnitude and unpredictability of this event are forcing companies to reconsider their decision-making processes (Norris et al, 2020). In fact, the pandemic had a huge impact not only on the economy but also from a social point of view (Nirino et al, 2022). Consequently, organizations have been forced to concentrate more on their social responsibility (He and Harris, 2020), thus increasing the relevance of social sustainable practices (Guaita Mart ınez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%